On the study of keyhole-mode melting in selective laser melting process - Le, Kim Quy (2020)
A physics-based computational fluid dynamics (CFD) model was developed to simulate selective laser melting (SLM) process. The heat source model imitates the multiple reflections of the laser beam by using the Fresnel absorption function. The model is able to simulate the fluid flow and heat transfer of keyhole-mode laser melting process, which is validated by single track experiments. In addition, the simulation results show that the melt pool dynamics of the well-deep keyhole is unsteady as compared to the medium-deep keyhole. Different modes of fluid flow, such as downward flow, bottom backward flow, clockwise flow and top forward flow are noticed in the well-deep keyhole melt pool. On the other hand, the melt pool dynamics of the medium-deep keyhole is more stable with two main flows of downward flow and backward flow. Furthermore, the model brings the benefit of predicting the keyhole-induced porosity within the solidified track.